WOMEN'S ANNIHILATION IN KIDS TV SHOW “SI BOLANG” - Mazda Radita Roromari (Profetik: Jurnal Komunikasi, 2023)
Si Bolang has aired in Trans7 since 2006 and achieved various awards as a kids-friendly show. However, this show never showed a girl as its main character and limited the appearance of women or girls. The contents of Si Bolang become a discourse representation of its producer. This research reviewed the women's discourse in the Si Bolang by elaborating on the screen's symbolic annihilation of girls and women. This research used Norman Fairclough's critical discourse analysis method to analyze through three dimensions: text, discourse practice, and social praxis. This research analyzed the full episode of Si Bolang uploaded on YouTube by the official account of Trans7. The perspective framework used in this research is the symbolic annihilation of Gaye Tuchman. The text analysis shows that there are absences of women or girls. They have a limited appearance and only appear in the domestic realm, which is also a form of trivialization. There are discourse practices of femininity, mothering, the culture of domesticity, and the division of work in the hunting-gathering society that influence Si Bolang's content. Women's annihilation and role restriction of women on the screen shows that Si Bolang formed from patriarchal discourse. This discourse tends to eliminate and limit women's role in society. Researchers need to review women's discourse in TV or other media kids' shows to encourage gender equality in Indonesia's media.